2012
DOI: 10.1128/jvi.06755-11
|View full text |Cite
|
Sign up to set email alerts
|

Pellino-1 Selectively Regulates Epithelial Cell Responses to Rhinovirus

Abstract: Pellino-1 has recently been identified as a regulator of interleukin-1 (IL-1) signaling, but its roles in regulation of responses of human cells to human pathogens are unknown. We investigated the potential roles of Pellino-1 in the airways. We show for the first time that Pellino-1 regulates responses to a human pathogen, rhinovirus minor group serotype 1B (RV-1B). Knockdown of Pellino-1 by small interfering RNA (siRNA) was associated with impaired production of innate immune cytokines such as CXCL8 from huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(62 citation statements)
references
References 30 publications
2
60
0
Order By: Relevance
“…These results may suggest that Pellino-1 is unlikely to affect host innate immune responses during infections by regulating microbial uptake or phagocytosis, but rather acts via potentiation of production of MyD88-and TRIF-dependent inflammatory cytokines. Notably, Pellino-1-deficient and sufficient human pulmonary bronchial epithelial cells had comparable replication of rhinovirus upon in vitro infection, whereas significant reduction of CXCL8 expression was noted in Pellino-1 Ϫ/Ϫ cells (40). Further studies are required to determine a currently unknown impact of Pellino-1 deficiency on microbial loads during infection in vivo and phagocytosis of live bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…These results may suggest that Pellino-1 is unlikely to affect host innate immune responses during infections by regulating microbial uptake or phagocytosis, but rather acts via potentiation of production of MyD88-and TRIF-dependent inflammatory cytokines. Notably, Pellino-1-deficient and sufficient human pulmonary bronchial epithelial cells had comparable replication of rhinovirus upon in vitro infection, whereas significant reduction of CXCL8 expression was noted in Pellino-1 Ϫ/Ϫ cells (40). Further studies are required to determine a currently unknown impact of Pellino-1 deficiency on microbial loads during infection in vivo and phagocytosis of live bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…PELI1 is important in regulating the innate immune response of the epithelium to rhinovirus infection, including CXCL8 production and neutrophil recruitment. 22 IRAK2 is critical in sustaining late-phase infl ammatory responses aft er TLR stimulation, which leads to increased cytokine production. 23 We have previously reported the upregulation of PELI1 and IRAK2 in response to rhinovirus infection of human primary bronchial epithelial cells in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that IRAK2 and PELI1 play a role promoting neutrophilic airway inflammation, which is triggered by RV infection of the epithelium in COPD. Recently, PELI1 has been shown to be important in regulating the innate immune response of the epithelium to RV, including CXCL-8 production and neutrophil recruitment, without interfering with IFN responses and viral replication [20]. Mouse models have shown that IRAK2 is critical in sustaining late phase inflammatory responses after TLR stimulation, leading to increased production of inflammatory cytokines [21].…”
Section: Discussionmentioning
confidence: 99%